A Study Comperative: the Perception of Coastal Communities in Developing the Method of Distribution of Marine Zakat - Diki S Riwanto (Center of Strategic Studies (PUSKAS) BAZNAS, 2017)
Indonesia as one of the largest maritime countries in the world that has enormous potential. The one of potential can be found at fishery resources reaching 6.4 million tons per year with the number of catch fisheries reaching more than USD 15 billion. Thus the total foreign exchange of marine and fishery reaches USD 71 million per year. But the facts, 83 percent of coastal communities are still living in poverty. To overcome these problems, it is necessary to optimize zakat, because in reality the implementation of zakat (in this case is marine zakat) is not optimal. This study is aimed to identify and develop the distribution model of marine zakat based on local people’s perception. In analyzing this research, the authors applied qualitative method through comparative study approach by using data collecting technique in the form of deep interviews. The object of this research is the people who live in Depok and Gunungkidul beach, Yogyakarta. Through this research, the authors hope the community can identify the development of the distribution model of marine zakat that can empower coastal communities and can motivate local people to be more productive and optimize the existence of this zakat. Keywords: Islamic Economics Marine Zakat, Empowerment Coastal Community, Maritime